Towards low-noise tunable terahertz waves generation via photomixing - Jamil Alsayaydeh, Jamil Abedalrahim; Indra, Win Adiyansyah; Irianto, Irianto; Khang, Adam Wong Yoon; Hassim, Nurulhalim; Herawan, Safarudin Gazali (Elsevier Ltd, 2026)
We demonstrate a low-cost, stable, and tunable laser system by phase-locking a commercial telecom-grade tunable laser (ITLA) to an Optical Frequency Comb (OFC) within the C-band. Using minimal optical hardware and sub-mW OFC power, we achieved short-term integrated phase noise of 10 mrad and long-term frequency stability of ±0.01 Hz over 10 h. This system enables scalable, OFC-locked tunable lasers and holds promise for applications like tunable THz wave generation and comb-locked transmitters in DWDM systems, supporting scalable phase-locking of multiple lasers with OFC power in the nW regime, making it highly adaptable for various OFC generators.